Pengembangan Media Pembelajaran PowerPoint-iSpring Pada Materi Redoks Kelas X SMA - Laras Santi; Guspatni Guspatni (Edukimia, 2022)
This research aims to develop PowerPoint-iSpring learning media on redox topic and determine its level of validity. This research used educational design research which is developed by Plomp. Research procedures consist of preliminary research stage, prototyping stage and  assessment stage. Instruments used was validation sheets consist of content, construct and media validity questionnaire, and one to one evaluation interview sheet. Subjects of this research were chemistry lecturers of FMIPA UNP, chemistry teachers as topic experts, engineering lecturers of FT UNP as media experts, and 10th grade students of SMAN 3 Mukomuko in the 2021 to 2022 academic year. Data obtained were analysed by using the Aikens V formula, and the results indicate that the PowerPoint-iSpring learning media on the redox material developed as a whole is valid. The average value of content validity for basic competency index 1, 2 and 3 is as followed 0.84, 0.83, and 0.83. The average value of construct validity for basic competency index 1, 2, and 3 is as followed 0.85, 0.86, and 0.85. The average value of media validity for basic competency index 1, 2, and 3 is 0.97.